Computational and experimental study on hole evolution and delamination in laser drilling of thermal barrier coated nickel superalloy. (August 2018) - Wang, Rujia; Duan, Wenqiang; Wang, Kedian; Dong, Xia; Fan, Zhengjie; Mei, Xuesong; Wang, Wenjun; Zhang, Shuai
Highlights: A thermal-mechanical coupled model for laser percussion drilling of thermal barrier coated nickel alloy was developed. The effects of laser parameters (pulse duration and laser power) and material property (elastic modulus) on delamination were discussed. Phenomenon of stagnation in laser percussion drilling appeared when peak power density dropped down. Stress mutation and thermal stress shock near the interfaces are responsible for the crack formation. Abstract: Computational study related to thermal stress and hole formation in laser percussion drilling of thermal barrier coated nickel alloy based on a thermal-mechanical coupled model, combined with experimental work, was conducted in this paper. The effects of laser parameters (pulse duration and laser power) and material property (elastic modulus) on delamination were discussed based on thermal stress analysis. Laser drilling with higher peak power density (>1e11W/m 2 ) can quickly get a through-hole of 2.3 mm within 10 pulses. Stress mutation and thermal stress shock near the interfaces are responsible for the crack formation. For the case with low peak power density, solidification rate and solidification sequence between materials should also be considered. Under the same pulse duration, the thermal stress would be enhanced with increasing of laser power. With the same pulse energy, a more intense thermal stress shock in pulse cycles can be produced under a longer pulse duration. And this shock effect near the interfaces can be alleviated when laser source is far from the interfaces. Heat accumulating effect induced by stagnation phenomenon, mainly due to lower peak power, can contribute to crack extension along the interfaces. Thus, breaking through the first two layers with high drilling efficiency is an effective way to restrain/prevent the delamination and viable parameters are also determined in the paper. Furthermore, it would offer great benefits for delamination prevention that make sure the elastic modulus of TBC and BC close to each other along the thickness with a gradually approaching method in their preparations.